Bound on some Diophantine equation - Amalulhair, N. H.; Sapar, S. H.; Johari, M. A. M. (Malaysian Mathematical Sciences Society, 2022)
Diophantine equation is known as a polynomial equation with two or more unknowns which only integral solutions are sought. This paper will concentrate on finding the least upper bound to the Diophantine equation x 2 + 2a 7 b = y n for 1 ≤ α ≤ 8 and found that there exists an integral solution to the equation for y = 2 and y > 2 with the bound on n < 15,000 and n < 11,000 respectively.